URGENSI PENYELENGGARAAN PENDIDIKAN DAN PELATIHAN BAGI PEGAWAI BADAN KEPEGAWAIAN DAERAH PROVINSI KALIMANTAN TIMUR - Rosa Anggraeiny; Rena Noviera; . Mahmudah (Magister Administrasi Publik FISIP Universitas Mulawarman, 2019)
Education and training is a necessity and is part of efforts to develop human resources as well as one solution to solving problems that occur in an organization, bureaucracy or government agency. Especially for the East Kalimantan Provincial Personnel Agency which has the main task of carrying out the preparation and implementation of staffing policies at the government level at the provincial level, then the development of employees through education and training is a necessity. This study found that education and training had been carried out for employees of the East Kalimantan Provincial Personnel Agency by presenting good instructors with good material, but the methods applied in training were still not appropriate. So that the goals and objectives of education and training are still not optimally achieved as expected, and require improvements related to the updating of the learning mehod. Keywords: education and training.